HMGA2 promotes vasculogenic mimicry and tumor aggressiveness by upregulating Twist1 in gastric carcinoma - Junying Sun (Nature Portfolio, 2017)
Abstract High mobility group protein A2 (HMGA2) is a transcription factor that plays an important role in the invasion and metastasis of gastric carcinoma (GC). The term vasculogenic mimicry (VM) refers to the unique ability of aggressive tumour cells to mimic the pattern of embryonic vasculogenic networks. However, the relationship between HMGA2 and VM formation remains unclear. In the present study, we examined concomitant HMGA2 expression and VM in 228 human GC samples and 4 GC cell lines. Our data indicate that HMGA2 is not only significantly associated with VM formation but also influences the prognosis of patients with gastric carcinoma. Overexpression of HMGA2 significantly increased cell motility, invasiveness, and VM formation both in vitro and in vivo. A luciferase reporter assay, Co-IP and ChIP demonstrated that HMGA2 induced the expression of Twist1 and VE-cadherin by binding to the Twist1 promoter. Moreover, we observed a decrease in VE-cadherin following Twist1 knockdown in cells overexpressing HMGA2. This study indicates that HMGA2 promotes VM in GC via Twist1-VE-cadherin signalling and influences the prognosis of patients with GC.